3D imaging and body measurement of riding horses using four scanners simultaneously - MATSUURA, Akihiro; TORII, Suzuka; OJIMA, Yuki; KIKU, Yoshio (Journal of Equine Science, 2024)
Although there have been advances in the technology for measuring horse body size with stereoscopic three-dimensional (3D) scanners, previously reported methods with a single scanner still face a significant challenge: the time necessary for scanning is too long for the horses to remain stationary. This study attempted to scan the horse simultaneously from four directions using four scanners in order to complete the scans in a short amount of time and then combine the images from the four scans on a computer into one whole image of each horse. This study also compared body measurements from the combined 3D images with those taken from conventional manual measurements. Nine riding horses were used to construct stereoscopic composite images, and the following 10 measurements were taken: height at the withers, back, and croup; chest depth; width of the chest (WCh), croup, and waist; girth circumference, cannon circumference (CaC), and body length. The same 10 measurements were taken by conventional manual methods. Relative errors ranged from −1.89% to 7.05%. The correlation coefficient between manual and 3D measurements was significant for all body measurements (P<0.01) except for WCh and CaC. A simple regression analysis of all body measurements revealed a strong correlation (P<0.001, R2=0.9994, root-mean-square error=1.612). Simultaneous scanning with four devices from four directions reduced the scanning time from 60 sec with one device to 15 sec. This made it possible to perform non-contact body measurements even on incompletely trained horses who could not remain stationary for long periods of time.